Qingdao TGOOD Electric Corporation - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
Founded in 2004, Qingdao TGOOD Electric Co., Ltd. (TGOOD) is a Sino-German joint venture high-tech enterprise headquartered in Laoshan District, Qingdao City, Shandong Province. The company designs and manufactures 220 kV (and below) primary and secondary power transformation and distribution products. It also provides related technical services. The products are complete sets of transformer and power distribution products. They are mostly outdoor cubicle-type power equipment supplemented by indoor switchgear cabinets. Its power transformation and distribution products and relevant technical services are offered to the railways, power companies, and coal-mining. TGOOD is the largest specialized developer and producer of cubicle-type transformation and distribution equipment in China, and ranks top in the railway, coal-mining, and local power markets. This case study examines this topic.